New data on aphids from Taimyr amber and systematic evaluation of the Taimyraphidoidea (Hemiptera: Sternorrhyncha) - B. Ogłaza; J. Brożek; E. E. Perkovsky; P. Wegierek (The European Zoological Journal, 2024)
Based on newly acquired inclusions in Taimyr amber, we have described new taxa (Sidorchukaphis katyae Ogłaza & Wegierek gen. et sp. nov.; Baikuraphis abdominalis gen. et sp. nov.; Canadaphis ugolyaki Ogłaza & Wegierek sp. nov.) of aphids or redescribed previously reported forms (Ambaraphis baikurensis Palaeoaphis incognita Tajmyraphis zherichini; Retinaphis glandulosa). The presented species belong to both extinct and extant families from the Late Cretaceous stage of aphid evolution. A cladistic analysis of the morphological characters of the Tajmyraphidoidea has been performed. We assign Burmitaphididae, as the subfamily Burmitaphidinae, to the Tajmyraphididae, which now comprises the subfamilies Tajmyraphidinae and Burmitaphidinae. We also suggest elevating the Mongolaphidinae to family rank (Mongolaphididae).http://www.zoobank.org/urn:lsid:zoobank.org:pub:2140429C-686C-4EE2-BF7A-67A368C1FFAC